Impact of using augmented reality applications in the educational environment. (November 2019) - Annafi, A; Hakim, D L; Rohendi, D
Abstract: This study discusses a literature review that focuses on the use of Augmented Reality in the educational environment. The author reviews articles published in the last 10 years that discuss the use of Augmented Reality in learning media at all levels of education. A total of 30 articles were analyzed thoroughly. The result shows various types of research methods were found and the levels of education varied from early childhood education, elementary school, junior high school, senior high school, vocational school, and tertiary education, even the technology was also used for students with special needs (disability). The research designs found also varied such as Experiment, Analysis, Action Research, Surveys, Mixed Method, and Research-Based and Development. The most prominent role of Augemented Reality in educational environment is to increase students' thinking ability, understanding, motivation, response, and learning outcomes towards the learning process. Most of the researches were conducted in secondary level while little attention was given in vocational level. Thus, this article would recommend to future studies to conduct more researches in vocational setting in order to display more evindence about the phenomenon of Augmented Reality in educational setting.